Isolation and molecular characterization of causal agent of blue mold on Allium cepa L. and its control by Pennisetum flaccidum Griseb - Tehzeeb Zubairi (Elsevier, 2021)
Blue mold pathogen, isolated from infected Allium cepa L., was identified as a Penicillium species through morphological and molecular characterisation. Internal Transcribed spacer (ITS) region of ribosomal DNA (rDNA) was utilised for DNA sequencing. Basic Local Alignment Search Tool (BLAST) analysis has found the maximum similarity index of the fungus to be 82.39% with the Uncultured Penicillium clone (Accession: MF535522). So, the isolated Penicillium specie is the first reported specie of the genus that infects onion. A phylogenetic tree was constructed to establish a relationship of the isolated fungus with the most relevant species reported on GenBank. Extracts of Pennisetum flaccidum Griseb. were evaluated against the isolated fungus as a potential biocontrol agent. Among the five tested methanol concentrations (0.5%, 1%, 1.5%, 2% and 2.5%) of each plant part (root, inflorescence and foliage), 0.5% root extract showed maximum growth retardation, i.e. 89%. For bioassay-guided fractionation, the root extract was partitioned in n-hexane, chloroform, n-butanol and ethyl acetate. Ethyl acetate (1%) was proved to be the most potent one. Phytochemical screening has confirmed the occurrence of terpenoids, tannins, saponins and alkaloids. The applied molecular approach has deduced that the Penicillium specie collected from Pakistan might be novel. This study can be concluded that P. flaccidum contains potent phytochemicals which might be used as antifungal agent against Penicillium species.